1977
DOI: 10.3382/ps.0560926
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial Activity of Salinomycin in Battery Raised Broiler Chickens

Abstract: Infections with single species of Eimeria acervulina, E. mivati, E. maxima, E. tenella, E. necatrix, and E. brunetti, and the six species mixed, were utilized in three separate battery experiments to evaluate the anticoccidial efficacy of various levels of salinomycin (AHR-3096), a fermentation product of a strain of Streptomyces albus. At the 60 to 100 p.p.m. treatment levels, this compound showed significant anticoccidial activity for all parameters studied (mortality, weight gain, feed conversion, dropping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Salinomycin is a monocarboxylic polyether antibiotic widely used as an anticoccidiosis agent in chickens (13,14). A recent study showed that salinomycin kills breast cancer stem cells at least 100 times more effectively than paclitaxel in mice (15).…”
mentioning
confidence: 99%
“…Salinomycin is a monocarboxylic polyether antibiotic widely used as an anticoccidiosis agent in chickens (13,14). A recent study showed that salinomycin kills breast cancer stem cells at least 100 times more effectively than paclitaxel in mice (15).…”
mentioning
confidence: 99%
“…Sal is a monocarboxylic polyether antibiotic already used as an antibacterial and anticoccidiosis drug. 12,13 Sal acts as an ionophore, 14 and promotes the transfer of cations across biological membranes via an exchange diffusion mechanism. As a result of this cation exchange, transmembrane gradients are altered, which in turn leads to changes in cell function and metabolism.…”
mentioning
confidence: 99%
“…Salinomycin has been shown to exhibit antimicrobial activity against gram-positive bacteria including mycobacteria and Staphylococcus aureus, some filamentous fungi, Plasmodium falciparum, and Eimeria spp., protozoan parasites responsible for the poultry disease coccidiosis (1,6,7). Therefore, salinomycin has been used for more than 30 years as an effective anticoccidial drug in poultry (8) and is also fed to ruminants and pigs to improve nutrient absorption and feed efficiency (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%